Diagnóstico do gerenciamento dos resíduos eletroeletrônicos no município de Missal - PR - Wili, Fernando (2018)
This study aimed to carry out a diagnosis of the management of electronic and electrical waste in the city of Missal, using questionnaires in companies that commercialize electrical and electronic products. In addition to this methodological procedure, data made available by the Secretariat of Agriculture and Environment regarding the generation and destination of the electric and electronic waste of the municipality of Missal were used. After data collection, they were classified, quantified, interpreted and analyzed in the form of tables, later they were contrasted with other studies already performed by other authors, as well as correlated with the literature pertinent to the subject in question. From the obtained results, it can be affirmed that the municipality of Missal plays an action, although incipient of adequate final destination for the residues of electrical and electronic products. In addition, companies that market electronic products in the municipality should improve the management of waste, presenting a statement of the appropriate destination. As a proposal to improve the management of the waste electrical and electronic equipment in the municipality of Missal, it is suggested to increase the number of collection points as well as the frequency of these collections, together with the population awareness projects and greater supervision of the competent bodies.